Monetary policy transmission through shadow and traditional banks - Amina Enkhbold (Bank of Canada, 2024)
I investigate how monetary policy transmits to mortgage rates via the mortgage market concentration channel for both traditional and shadow banks in the United States from 2009 to 2019. On average, shadow and traditional banks exhibit only a slight disparity in transmitting monetary shocks to mortgage rates. Nonetheless, in highly concentrated mortgage markets, shadow banks transmit marginally 35 basis points (bps) more, whereas traditional banks transmit marginally 25 bps less in response to a monetary policy surprise of more than 100 bps. Lastly, banks serve different parts of the mortgage rate distribution: (i) fintech lenders compete with traditional banks for the highest rates, (ii) traditional banks target primarily the middle of the mortgage rate distribution, and (iii) non-fintech lenders specialize in the lowest rates by transmitting monetary policy the least.
Keywords: E44; E52; G21; 330; Financial institutions; Interest rates; Monetary policy transmission